Green finance and foreign direct investment–environmental sustainability nexuses in emerging countries: new insights from the environmental Kuznets curve - Qadri, Syed Usman; Shi, Xiangyi; Rahman, Saif ur; Anees, Alvena; Ali, Muhammad Sibt E.; Brancu, Laura; Nayel, Ahmad Nabi (Frontiers in Environmental Science, 2023)
The prime objective of the present study is to identify the asymmetric relationship between green finance, trade openness, and foreign direct investment with environmental sustainability. The existing research utilizes the asymmetric approach to evaluate the annual data from 1980 to 2021. The findings of the study show heterogeneous results. Therefore, the outcomes of the study confirm the nonlinear (NARDL) association between the variables in Pakistan. Moreover, the study describes the positive shock of FDI as a significant and positive relationship with environmental degradation, and the negative shock of FDI shows a negative and significant relationship with the environment. Furthermore, the study scrutinizes the positive shock of green finance as a significant and negative relationship with environmental degradation, and the negative shocks also show a negative relationship with environmental degradation in Pakistan. In addition, the consequences of the study suggest the government should implement some taxes on foreign investment and suggest that investors use renewable energy for the production of goods. Furthermore, the study suggests that the government should utilize fiscal policy and fiscal funds to enhance carbon-free projects. Moreover, green securities should be used for green technologies. However, Pakistan can control its carbon emissions and achieve the target of a sustainable environment. Therefore, Pakistan’s government should stabilize its financial markets and introduce some carbon-free projects. Furthermore, the main quantitative achievement according to the outcomes is to suggest that policymakers make some policies in which they suggest to the government to control the foreign investment which causes by carbon emissions because of trade openness and also invest the funds in renewable energy which helps to control the carbon emissions. Keywords: environmental degradation, trade openness, green finance, economic growth, NARDL approach JEL classification: F65, F64, E12, F31, F21, C32